Didactic conditions for the effective use of digital technologies in the training of students of humanities specialties - Zuiev, Mykhailo (Educological discourse, 2026)
The article substantiates the didactic conditions for the effective use of digital technologies in the training of students of humanities specialties at a Ukrainian university. The relevance of the study is due to the institutional transition to mixed and distance formats, uneven access to resources, and the need to ensure quality and academic integrity in the digital environment, in particular in conditions of military risks. The goal is to scientifically and methodologically substantiate the system of didactic conditions that transform the use of digital tools from technical support of the course into a pedagogically guided tool for the development of humanitarian learning outcomes (critical reading, argumentation, academic writing, working with sources and data). The methodology is of a theoretical and methodological nature and includes a documentary analysis of normative and contextual materials, a scoping review of scientific publications, qualitative content analysis, and pedagogical modelling with subsequent operationalization of the results in the form of a methodological matrix. Five interrelated didactic conditions were obtained: (1) constructive coordination of learning outcomes, educational activities, and assessment; (2) activity-based and scenario-based design of activities in a digital environment with phased support; (3) organizational and infrastructural sustainability and accessibility (a minimally sufficient set of tools, asynchronous alternatives, clear course structure); (4) formative assessment, feedback, and academic integrity, including rules for responsible use of AI; (5) digital pedagogical competence of the teacher and systemic support of students. The practical significance lies in the proposed matrix “condition – indicators – digital-methodological solutions – expected results – evidence/assessment”, which can be used to design disciplines of the humanitarian cycle, develop tasks and rubrics, organize feedback, and increase the sustainability of learning in the Ukrainian context.